Strategi Guru Agama Kristen dalam Membentuk Karakter Generasi Muda di Era Industri 4.0 - Edison; Talizaro Tafonao (Jurnal Shanan, 2021)
This study departs from problems that often occur in the industrial era 4.0, where the behavior of young people today causes many negative symptoms in social life in society. One of the characteristics of the younger generation that can be seen in the industrial era 4.0 is the lack of a sense of concern and tends to be individual and live in carelessness that always opposes the values ​​of truth and prevailing culture. The purpose of writing this article is to see how the efforts made by Christian religious teachers in shaping the character of the younger generation in accordance with Christian values. The method used is a qualitative method by examining the extent of the problems caused by the character of the younger generation in the industrial era 4.0. The analysis process is carried out using various sources of literature, both articles, books, interviews and direct observations to support the author's analysis. The results found are significant about the role of Christian teachers supported by various strategies in shaping the character of the younger generation in the era of the industrial revolution 4.0. Thus, the responsibility of Christian Religion teachers in educating generations really needs to be realized as a form of concern for the phenomena that exist among young people as explained in this article.